Prevalence and nature of lung function abnormalities among Indigenous Australians referred to specialist respiratory outreach clinics in the Northern Territory. Issue 2 (12th February 2019) - Schubert, Jonathon; Kruavit, Anuk; Mehra, Sumit; Wasgewatta, Sanjiwika; Chang, Anne B.; Heraganahally, Subash S.
Abstract: Background: Poor lung function is a predictor of future all‐cause mortality. In Australia, respiratory diseases are particularly prevalent among the indigenous population, especially in remote communities. However, there are little published pulmonary function tests' (PFT) data of remote‐based adult indigenous patients. Aim: To evaluate the severity of airflow obstruction and other PFT abnormalities of adults referred to specialist respiratory clinics in remote indigenous communities. Methods: Retrospective analysis of PFT (pre‐ and post‐bronchodilator spirometry, total lung capacity (TLC) and diffusing capacity to carbon monoxide (DLCO)) of indigenous patients collected during specialist respiratory clinics in remote Northern Territory (NT) indigenous communities (Australia) between 2013 and 2015. The National Health and Nutrition Examination Survey (NHANES) III without ethnic correction was used as the reference. Results: Of the 357 patients, 150 had acceptable spirometry, and 71 had acceptable DLCO and TLC studies. Despite the relatively young age (mean = 49 years, SD = 12.9), their lung function was generally low; mean % predicted values were FEV1 = 55% (SD = 20.5%), FVC = 61% (SD = 15.6%), DLCO = 64.0% (SD = 19.7%) and TLC = 70.1% (SD = 18.2%). Mean FEV1 /FVC ratio was preserved (0.71, SD = 0.16). Post‐bronchodilator airflow obstruction (FEV1 /FVC < 0.7) was observed in 37% of patients, where a large proportion (67%) demonstrated at least a severe airflow obstruction, with a mean FEV1 of 41% predicted. Conclusion: In this first study of PFT findings of indigenous adults from a remote‐based clinical service, we found a high rate of at least moderate airflow limitation and low FVC along with preserved FEV1/FVC ratio. Increased awareness and screening for reduced lung function needs to be considered in this population.